The Influence of Experiential Marketing on Customer Loyalty Through Customer Satisfaction as the Mediating Variable: Study at Food and Beverages Restaurant in Pontianak and Kubu Raya District - Sanjaya, Ericson B1024151010 (Jurnal Manajemen Update, 2019)
The purpose of this research is to analyze the influence of Experiential Marketing to Customer Loyalty through Customer Satisfaction as the Mediating Variable in Food and Beverages Restaurant in Pontianak and Kuburaya District. The competition in culinary of Food and Beverage Restaurant is increasingly significant improving. In Culinary business sector is commonly known as a vulnerable business when it comes to the problem of the food taste consistency and service provided. From this point, the culinary businessmen of food and beverages restaurant want and need to make the customer satisfied and loyal to their businesses. From this point we can see that it is undeniable Customer loyalty plays an important factor in every industry, especially in creative industry such as culinary sectors. While Experiential Marketing with its 5 dimensions is used as the strategy to achieve the Customer Loyalty. The data obtained in this research by distributing the online questionnaires and the data is analyze Structural Equation Model Partial Least Square (SEMPLS) method. To conduct analysis using PLS method, this research is using smartPLS 3.0 software. The hypothesis of the research are. The result of this research shows that H2, H5, H6, H11, and H12 are accepted but H1. H3, H4, H7, H8, H9, and H10 are rejected. Keyword : experiential marketing, customer loyalty, customer satisfaction, sensory experience, affective experience, creative cognitive experience, physical experience, social identity experience References Abdillah, W., & Hartono, J. (2015). Partial Least Square (PLS): Alternatif Structural Equation Modelling (SEM) dalam Penelitian Bisnis. Yogyakarta: Penerbit Andi.Abraham, M. R. (2009). Importance of a Theoritical Framework for Research. Nuts and Bolts of Chemical Education Research, 976: 47-66.Ajayi, V. O. (2017). Distinguish between primary sources of data and secondary sources of data. journal from BENUE STATE UNIVERSITY, MAKURDI.Alkilani, K. C., & Abzakh, A. A. (2013). the Impact of Experiential Marketing and Customer Satisfaction on Customer Commitment in the World of Social Networks. Asian Social Science: Vol. 9 No. 1: 2013, http://dx.doi.org/10.5539/ass.v9n1p262.Alreck, P., & Settle, R. (2003). Survey Research Handbook (3rd ed). Newyork: Mcgraw-Hill Education.Amir, H. (2007). Analisis Experiential Marketing , Emotional Building, dan Brand Trust Terhadap Loyalitas Merek Mentari. Manajemen Ushawan Indonesia (MUI), No. 06/Th.36/Juni 2007.Andreani, F. (2007). Experiential Marketing (Sebuah Pendekatan Pemasaran). Jurnal Manajemen Pemasaran Volume 2 No 1, 7.Araci, E. U., Bulut, A. Z., & Kocak. (2017). The Relation Among Experiential Marketing, Customer Satisfaction, and Behavioral Intention: A Study on Food and Beverage Business. 23rd International Scientific Conference on Economic and Social Development.Araci, U. E., Bulut, Z. A., & Kocak, N. (2017, September). The Relation Among Experiential Marketing, Customer Satisfaction, and Behavioral Intention; A Case Study on Food and Beverage Business. 369.Baron, R. M., & Kenny, D. A. (1986). The Moderator-Mediator Variable Distinction in Social Psychological Research: Conceptual, Strategic, and Statistical Considerations. Journal of Personality nd Social Physchology, 51 (6), 1176.Chang, Y. S., & Lee, T. H. (2011). Leisure StudiesISSN 0261-4367 print/ISSN 1466-4496 online© 2012 Taylor & Francishttp://www.tandfonline.comThe influence of experiential marketing and activity involvement on the loyalty intentions of wine tourists in Taiwan. Leisure Study.Cohen, J., P, C., West, S. G., & Aiken, L. S. (2003). Applied Multiple Regression/Correlation analysis in the behavioral sciences (3rd ed). Mahwa, NJ: Erlbaum. p. 76.Cooper, D. R., & Schindler, P. S. (2014). Business Research Methods. Newyork: McGraw-Hill/Irwin.Dian, Y. (2012). Analysis of pengaru Experiential Marketing, customer quality,customer satisfaction and customer loyalty. Jogjakarta: Journal manejemen and Business UGM.Ekoputra, A., Hartayo, & Nurrochmat, D. (2017). The Effect of Experiential Marketing on Customer Satisfaction and Loyalty Restaurant 150 Eatery in Bogor. International Journal of Science and Research (IJSR).Etikan, I., & Bala, K. (2017). Sampling and Sampling Methods. Biometrics & Biostatistic International Journal, 5(6).Fung, H. P. (2017). How do you determine the validity and reliability of a new questionaire? Online. Available at: https://www.reserachgate.net/post/How_do_you_determine_the_validity_of_a_questioanire, Accessed on 21 January 2019.Ghozali, I. (2012). Aplikasi Multivariate dengan Program IBM SPSS 21 (21st ed). Semarang: Undip.Google Data, I. (2019). Restoran di Pontianak dan Kubu Raya. Available at: https://www.google.com/search/restoran+di+pontianak+dan+kubu+raya, Acccess on 28 February 2019.Hair, J., & Celsi, M. (2011). Essentials of Business Reseach Methods. Newyork: M.E Sharpe.Hansemark, O. C., & Albinsson, M. (2004). Customer Satisfaction and Retention: The Experiences of Individual Employees Managing Service Quality. 14 (1), pp. 40-57.Hasan, A. (2009). Marketing Edisi Baru. Jogjakarta: Medpress.Husein, U. (2008). Metode Penelitian untuk Skripsi dan Tesis Bisnis. Jakarta: PT. Rajagrafindo Persada.Hutama, A. C. (2014). Pengaruh customer experience, service quality dan product quality terhadap customer loyalty melalui customer satisfaction sebagai variabel intervening pada kafe bangi kopitiam di Spazio Surabaya. Masters thesis, Widya Mandala Catholic University Surabaya.J.J, H., & Bechger, T. (2011). An Introduction tp Structural Equation Modelling. Family Science Review, 11, 354-373.Kalla, S. (2011). Relationship Between variables Online. Available at: https://exploreable.com/relationship-between-variables, Accessed on 19 January 2019.Kartajaya, H. (2006). HermawanKartajaya on Marketing. Jakarta: PT. Gramedia Pustaka Utama.Kennedy. (2008). The importance of good sampling [Online]. available at: http://www.coronainsights.com/2008/08/the-importance-of-good-sampling/, Accessed on 21 January 2019.Khadka, K., & Maharjan, S. (2017). CUSTOMER SATISFACTION AND CUSTOMER LOYALTY. Journal from Centria Universityof Applied Sciences of Pietaarsari, 9.Kotler, P., & Armstrong, G. (2014). Principles of Marketing (15 ed). Harlow, England: Pearson Education Limited.Kotler, P., & Keller, K. L. (2012). Marketing Management (14 ed). Harlow, England: Pearson Education Limited.Kuncoro, M. (2009). Metode Riset untuk Bisnis & Ekonomi. Jogjakarta: Penerbit Erlangga.Lazuardi, M., & Triady, M. (2015). Ekonomi Kreatif: Rencana Pengembangan Kuliner Nasional. PT. Republik Solusi.Lovelock, C., & Wirtz, J. (2014). Service Marketing (7th Ed). London: Pearson Education.Maghnati, F. K. (2012). Exploring the Relationship between Experiential Marketing and Experiential Value in the Smartphone Industry. International Business Research, 5(11), pp: 169-177.Margaretha, M. (2004). Studi mengenai loyalitas pelanggan pada divisi asuransi kumpulanAJP bumi Putra. Jurnal Sains Pemasaran Indonesia,Vol. iii, No. 3, 289-308.Mattila, A. A. (2001). Emotional bonding and restaurant loyalty. Cornell Hotel and Restaurant Administration Quarterly, 42(6), 73-79.McMillan, & James, H. (2011). Educational Research:Fundamental for the Consumers, 2nd ed. pp. 258-359.Megawati, S. (2012). The Influence of Experiential Marketing to Customer Loyalty at Pondok Patin Restaurant in Pekanbaru. JURNAL MANAJEMEN UNIVERSITAS RIAU 2012.Ming Lin, K., Ming, C., Pin Lin, Z., Lang Tseng, M., & Lan, W. L. (2009). Application of Experiential Marketing Strategy to Identify Factors Affecting Guests’ Leisure Behavior in Taiwan Hot-Spring Hotel. WSEAS TRANSACTIONS on BUSINESS and ECONOMICS.Mohsan, F. N. (2011). Impact of customer satisfaction on customer loyalty and intentions to switch: Evidence from banking sector of Pakistan. International Journal of Business and Social Science, 3(4): 72–80.Musfar, F., & Novia, V. (2012). Pengaruh Experiential Marketing terhadap Custmer Loyalty pada Pelanggan Restoran Koki Sunda di Pekan Baru. Jurnal Ekonomi Volume 20, Nomor 4 Desember 2012.Oliver, R. (1997). Satisfaction as Behavioral Perspective on the Customer. Newyork: McGraw-Hill.O'Shaughnessy, J. A., & O'Shaughnessy, N. J. (2003). The Marketing Power of Emotion. Oxford: Oxford University Press.Ozturk, R. (2015). Exploring the Relationship Between Experiential Marketing Customer Satisfaction and Customer Loyalty: An Empirical Examination in Konya. International Journal of Social, Behavioral, Educational, Economic and Management Engineering Vol:9, No:8, 2015.Peter, P., & Olson, J. (1999). Prilaku Konsumen dan Strategi Pemasaran (4th ed). Jakarta: Erlangga.Pine II, J., & Gilmore, J. H. (1998). Welcome to the Experience Economy. Harvard Business Review, 97-98.Piotr, Z. (2004). Technical Analysis as the Representation of Typical Cognitive Biases. International Review of Financial Analysis, 13(2), 217-225.Popham, W. J. (2008). Transformative Assessment. United States: Houghton Mifflin Harcourt.Prasetyo, B., & Jannah, L. M. (2012). Metode Penelitian Kuantitativ (7th ed). Jakarta: Rajagrafindo Persada.Sangadji, E. M., & Sopiah. (2010). Metodologi Penelitian: Pendekatan Praktis dalam Penelitian. Jogjakarta: Penerbit Andi.Schmitt, B. H. (1999). Experiential Marketing: How to get Customers to Sense, Feel, Think, Act, and relate to Your CompanyBrands. Newyork: The Free Press.Sekaran, U. (2003). Research Method for Business. John Wiley & Son.Sekaran, U., & Bougie, R. (2011). Research Methods for Business: skill-Building approach (1st ed). United Kingdom: John Wiley & Sons Ltd.Sekaran, U., & Bougie, R. (2013). Research Methods for Business. United Kingdom: Jhon Wiley & Sons Ltd.Sugiyono. (2014). Metode Penelitian Pendidikan Pendekatan Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.Tao, F. (2014). Customer Relationship management based on Increasing Customer Satisfaction. International Journal of Business and Social Science, Volume. 5, Issue. 5 ,pp: 256-263.Thomas, B. &. (2013). Anticipate: Knowing what customers need. NeW Jersey: John Wiley & Sons.Utarsih, H. (2016). Pengaruh Experiential Marketing, Customer Relationship Marketing, dan Customer Satisfaction terhadap Customer Loyalty Hotel Bintang 3 sampai dengan 5 di kota Bandung. Jurnal Indonesia Membangun.Vinzi, V. E., Chin, W. W., Henseler, J., & Wang, H. (2010). Handbook of Partial Least Square: Concepts, Methods and Applications. Newyork: Springer Publication.Wahyudi, S., & Lavinia, J. (2017). Analisa Pengaruh Experiential Marketing Terhadap Customer Loyalty dengan Customer Satisfaction sebagai Variabel Mediasi pada Restoran Jepang dengan Konsep Shabu-Shabu di Surabaya. Jurnl Program Manajemen Perhotelan, Fakultas Ekonomi, Universitas Kristen Petra.Wahyuningtyas, F. M., Achmad, F., & Zainul, A. (2017). The Effect of Experiential Marketing on Satisfaction and its Impact on Customer Loyalty. RJOAS, 1(61), January 2017.Widowati, R., & Fitria, T. (2017). The Influence Of Experiential Marketing On Customer LoyaltyThrough Customer Satisfaction As Intervening Variable. Universitas Muhammadiyah Yogyakarta Journal Vol 8, 166.Zena, A. P., & Hadisumarto, A. D. (2012). The Study of Relationship among Experiential Marketing, Service Quality, Customer Satisfaction, and Customer Loyalty. ASEAN MARKETING JOURNAL, June 2012 - Vol.IV - No. 1.Zikmund, W. (2010). Business Research Methods (8th ed). Canada: Cengange Learning.